Mutational landscape of plasma cell-free DNA identifies molecular features associated with therapeutic response in patients with colon cancer. A pilot study - Cervena, Klara; Pardini, Barbara; Urbanova, Marketa; Vodenkova, Sona; Eva, Pazourkova; Veskrnova, Veronika; Levy, Miroslav; Buchler, Tomas; Mokrejs, Martin; Naccarati, Alessio; Vodicka, Pavel; Vymetalkova, Veronika (Mutagenesis, 2021)
Cell-free DNA (cfDNA) has recently been used as a non-invasive diagnostic tool for detecting tumour-specific mutations. cfDNA may also be used for monitoring disease progression and treatment response, but so far researchers focused on one or few genes only. A genomic profile may provide better information on patient prognosis compared to single specific mutations. In this hypothesis-generating study, we profiled by whole exome sequencing serial plasma samples from 10 colon cancer (CC) patients collected before and after 5-fluorouracil-based therapy, and one year after diagnosis to determine alterations associated with treatment response. In parallel, genome profiling was also performed in patients' corresponding tumour tissue to ascertain the molecular landscape of resistant tumours. The mutation concordance between cfDNA and tumour tissue DNA was higher in more advanced tumour stages than in the early stages of the disease. In non-responders, a specific mutation profile was observed in tumour tissues (TPSD1 p.Ala92Thr, CPAMD8 p.Arg341Gln, OBP2A p.ArgTyr123CysHis). A pathogenic APC mutation (p.Ser1315Ter) was detected only in cfDNA of one poor responder one year after the diagnosis and after therapy termination. Another poor responder presented a likely pathogenic TP53 mutation (p.Arg110Pro) in cfDNA of all plasma samplings and in tumour tissue. In conclusion, cfDNA could be used for genetic characterisation of CC patients and might be clinically useful for non-invasive therapy response monitoring.
Keywords: senioři; DNA, Neoplasm; Sequence Analysis, DNA; Prognosis; Neoplasm Grading; fluoruracil; Fluorouracil; Middle Aged; mužské pohlaví; mutace; Biomarkers, Tumor; nádory tračníku; Neoplasm Staging; ženské pohlaví; nádorové biomarkery; prognóza; Mutation; Humans; High-Throughput Nucleotide Sequencing; Cell-Free Nucleic Acids; DNA nádorová; Colonic Neoplasms; lidé středního věku; stupeň nádoru; volné cirkulující nukleové kyseliny; vysoce účinné nukleotidové sekvenování; sekvenční analýza DNA; staging nádorů; Female; Aged; lidé; Male